Development of thinking and language skills. From the problem to the solution - Peña Guerrero, Nelsy (Omnia, 2024)
Thinking and language are topics that all teachers in educational institutions must assume. The purpose of the article was to analyze the problem of the low level of development of thinking and language skills from three perspectives: results in national and international tests, educational reforms and teachers' conceptions. The study is mainly supported by the contributions of Ritchhart & Church (2020), Swartz (2018), Robinson (2016). Methodologically, it had a documentary design with a descriptive scope, which reviews the Colombian educational reforms of the last 25 years, complemented with a qualitative exercise that collects, through a structured interview, the conceptions about thinking and language teaching that a group of First Year teachers have. Primary Education Cycle of Colombia. It is essential to adopt a comprehensive and contextualized approach to these aspects. It involves migrating from traditional methods to dynamic, student-centered practices. Only in this way can we guarantee an education that forms thinking, creative and communicative citizens, prepared to live together in today's world